2020
DOI: 10.20473/jipk.v12i1.17963
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Litter as Pollutant in the Aquatic Environment: A mini-review

Abstract: HighlightThe issue of plastic litter and microplastics which is currently of special concern in global particularly IndonesiaThe review of size, colour and shape of microplastics that becomes part of the plastic litterThe observed review highlight of plastic litter and microplastics impact on environmental health particularly aquatic biotaAbstractThe negative impact that comes from plastic litter in the aquatic environment is a scourge for the entire world including Indonesia.Plastic litter has a huge influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 88 publications
(74 reference statements)
0
7
0
3
Order By: Relevance
“…Kegiatan pariwisata secara masif yang menjadi ciri dari perkembangan kawasan wisata (Poedjiastoeti et al, 2022) pun dapat mengakibatkan kerusakan ekosistem mangrove. Kegiatan pariwisata berpotensi menjadi sumber sampah plastik, khususnya mikroplastik yang akan terkumpul dalam sedimen dan mengganggu keseimbangan ekosistem mangrove serta rantai makanan biota yang berasosiasi didalamnya (Anggraini et al, 2020). Sampah plastik merupakan penyebab dari matinya pohon mangrove karena dapat menghalangi atau menghambat proses fotosintesis dan bibit pohon banyak terbawa atau terseret ke laut (Li et al, 2018).…”
Section: Pendahuluanunclassified
“…Kegiatan pariwisata secara masif yang menjadi ciri dari perkembangan kawasan wisata (Poedjiastoeti et al, 2022) pun dapat mengakibatkan kerusakan ekosistem mangrove. Kegiatan pariwisata berpotensi menjadi sumber sampah plastik, khususnya mikroplastik yang akan terkumpul dalam sedimen dan mengganggu keseimbangan ekosistem mangrove serta rantai makanan biota yang berasosiasi didalamnya (Anggraini et al, 2020). Sampah plastik merupakan penyebab dari matinya pohon mangrove karena dapat menghalangi atau menghambat proses fotosintesis dan bibit pohon banyak terbawa atau terseret ke laut (Li et al, 2018).…”
Section: Pendahuluanunclassified
“…The low H'′ and high RA which is observed among planktonic and pollution resistant species as shown in the E Java N coast, was associated with higher pollution levels in this region (c.f. Risjani et al, 2014Risjani et al, , 2020aAnggraini et al, 2020a;Triaji et al, 2017), which originated from plastic litter (Anggraini et al, 2020b;Buwono et al, 2021) and other anthropogenic waste. Sediment load was an effect of the riverine discharge from the adjacent delta and largely originated from the volcanic mud and revealed that organic rich sediments of the delta retained genotoxic compounds (Risjani et al, 2020a).…”
Section: Biodiversitymentioning
confidence: 99%
“…Pernyataan tersebut diperkuat oleh Widianarko dan Hantoro (2018), menyatakan bahwa mikroplastik tipe filamen juga digolongkan dalam mikroplastik tipe serat, karena bentuknya yang seperti serat, tetapi berbeda bentuknya dengan tipe fiber yang seperti benang. Menurut Anggraini et al, (2020) mikroplastik tipe filamen adalah partikel polimer plastik yang berasal dari fragmentasi kantong plastik atau kemasan plastik dan memiliki kepadatan atau volume yang sangat rendah.…”
Section: Gambar 7 Udang Famili Palaemonidaeunclassified